Pregnancy after Cytoreductive Surgery and Hyperthermic Intraperitoneal Chemotherapy in Pseudomyxoma Peritonei - Renato Gomes Campanati; Bernardo Hanan; Sérgio Simões de Souza; Rodrigo Gomes da Silva (Case Reports in Surgery)
Pseudomyxoma peritonei is usually a benign tumor that is slightly more common in women. However, it requires aggressive surgical treatment and chemotherapy, often compromising future reproductive function. This report presents a case of pregnancy in a 35-year-old woman who underwent cytoreductive surgery and hyperthermic intraperitoneal chemotherapy for treatment of pseudomyxoma peritonei. The tumor was diagnosed during a laparoscopic examination on a workup for infertility in 2008. Two months later, she underwent a peritonectomy followed by hyperthermic intraperitoneal chemotherapy and, regarding her will to conceive, ovaries and fallopian tubes were preserved. In March 2011, she went through an in vitro fertilization followed by an uneventful pregnancy and delivered a healthy child 39 weeks later. Ovaries are usually resected during the cytoreductive surgery, since they are common sites for neoplastic implants, and, even when not performed, little is known about the effects of local chemotherapy on female fertility. The largest international survey on this matter only describes seven similar cases. This particular report not only describes a rare condition but also adds to the upcoming discussion about whether ovaries can be preserved in specific situations, therefore keeping the prospect of conceiving after this treatment.